Business and Politics in Indonesia - MACINTYRE, Andrew (Allen & Unwin, 1992)
Business and Politics in Indonesia" focuses on the ways in which sections of business attempt to organize themselves to secure a voice in the policy-making process and it throws light upon key elements of the political system. It puts forward an argument which challenges the prevailing view that the government is able to control the political system tightly. Forces of economic and political change at work in Indonesia are facilitating a new assertiveness by some business groups and are loosening the government's grip on the policy process. "Business and Politics in Indonesia" provides a close analysis of the ways in which government and industry actually interact in the formation of policy, and the book ties this to a wider assessment of the direction of political change in Indonesia. Andrew MacIntyre has conducted extensive research into the dynamics of relations between government and business in Indonesia, as well as in Thailand and South Korea. He currently lectures in political science in the Division of Asian and International Studies, at Griffith University in Brisbane. This book is intended for students and researchers in Asian studies, and politics.